The Role of Mobile Applications in Increasing Digital Literacy Among Students - Yayuk, Erna; Ekowati, Dyah Worowirastri; Restian, Arina; Deviana, Tyas (Jurnal Pendidikan Progresif, 2025)
The Role of Mobile Applications in Increasing Digital Literacy Among Student. Objective: This study aims to analyze the role of mobile applications in improving digital literacy among students. Digital literacy, which includes the ability to use information technology effectively and safely, is an important skill in the digital era. Methods: This study used a quantitative approach with an experimental design, involving 200 students from Pre-Service Elementary Teacher at Universitas Muhammadiyah Malang. Data was collected through a questionnaire that measured the level of digital literacy of students before and after using education-based mobile applications. Results: The results of the study show that the use of education-based mobile applications can improve students' skills in seeking information, managing digital media, and interacting safely in cyberspace. Students who use applications with interactive features, such as quizzes and learning materials, have experienced significant improvements in their understanding of digital literacy. In addition, student motivation and active involvement were also found to affect the effectiveness of using applications in improving digital literacy. Conclusion: The conclusion of this study is that education-based mobile applications have great potential in improving students' digital literacy. Therefore, the integration of mobile applications in the formal learning process is highly recommended to prepare learners to face the challenges of the ever-evolving digital world. Keywords: mobile applications, digital literacy, students, interactive learning.